Simulating the pedestrian movement in the public transport infrastructure - Bohari, Zulfadly Azizi; Mohamed Osman, Mariana; Bachok, Syahriah (Elsevier, 2016)
Aiming at assessing accurately and effectively of the mass people movement in public transport infrastructure, this research adopting video recording to capture the movement, direction, and demographic data of the users. This research associated with Siliconcoach software to support the data analysis such as walking speed, most occupied exits and routes. Such analyzed data then processes in the SimWalk software to allow the 2D visualization of the movement of each user as an animation which taking into account the factors such as users’ characteristics; their familiarity with the attributes of the environment. Hence the output of the simulation beneficial in contributing towards planning and designing of potentially crowding public spaces in the future.